Biological properties of foot-and-mouth disease virus А 2205/G-IV strain - M. V. Sidorovskaya; S. N. Fomina; V. V. Nikiforov; T. A. Komarova; M. A. Shevchenko; N. A. Kolchanov; S. R. Kremenchugskaya (Ветеринария сегодня)
According to the World Organisation for Animal Health, foot-and-mouth disease (FMD) is regularly reported in domestic and wild cloven-hoofed animals in Africa. G-I, G-IV, G-VI, G-VII, ASIA/Iran-05 genetic lineages of serotype А FMD virus are considered to be the most widespread on the African continent. Given the close economic and trade relations maintained by the Russian Federation with the countries of North Africa, of particular interest for us is studying the FMD virus of serotype A G-IV genetic lineage, which has been responsible for the infection outbreaks in the naturally susceptible animal population of the said region every year since 2012, and there is a risk of introduction of this virus genotype in to the Russian Federation. Therefore, the issues of FMD introduction risk assessment and timely diagnosis are relevant for the Veterinary Service of Russia. FMD virus A 2205/G-IV strain tested for its biological and antigenic properties in cell cultures and naturally susceptible animals (cattle and pigs) was adapted for its reproduction in initially trypsinized porcine kidney (PK) cell culture, continuous monolayer cell cultures (IB-RS-2, PSGK-30, YaDK-04, ВНК-21) by five serial passages. The virus was considered to be adapted when 90–95% cytopathic effect developed within 14–19 hours after the cell culture infection. The virus adapted to the cell cultures was tested for its infectivity with microtitration in IB-RS-2 cell culture. The virus strain tested for vaccine matching with microneutralization test (MNT) demonstrated significant difference from production A/Turkey/06, А22 No. 550/Azerbaijan/64, A22/Iraq/64, A/Iran/97, A No. 2155/Zabaikalsky/2013, A No. 2166/Krasnodarsky/2013, A No. 2269/ARRIAH/2015 strains of FMD virus.